2022
DOI: 10.3389/fmars.2022.1040681
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and chemical composition of the eastmost deep-sea anoxic brine pools in the Eastern Mediterranean Sea

Abstract: Deep-sea anoxic brine pools are unique and extreme, yet habitable environments. However, their extent and processes of formation are not fully understood. Using geophysical analysis and seafloor surveying, we discovered the eastmost brine pools known in the ultraoligotrophic Eastern Mediterranean Sea, at the Palmahim Disturbance offshore Israel (~1150 m water depth). These brine pools are located directly above a ~1km wide piece of the Messinian evaporites section, which was up thrusted to ~350 m below the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 70 publications
2
35
1
Order By: Relevance
“…Fluids with a low-Mg/Ca ratio (<2) are a prerequisite for the precipitation of LMC (Stanley et al, 2002). Possible sources of fluids with low-Mg/Ca ratios are Mg depleted and Ca enriched brine seeps, with such an example recently found in the vicinity of the studied sites (Charlou et al, 2003;Herut et al, 2022;Huguen et al, 2009). The 18 O values of the Palmahim brine pools (+2.0‰ VSMOW ) are slightly enriched compared to ambient sea water (+1.5‰ VSMOW ; Herut et al, 2022).…”
Section: Lmc Cementsmentioning
confidence: 88%
See 1 more Smart Citation
“…Fluids with a low-Mg/Ca ratio (<2) are a prerequisite for the precipitation of LMC (Stanley et al, 2002). Possible sources of fluids with low-Mg/Ca ratios are Mg depleted and Ca enriched brine seeps, with such an example recently found in the vicinity of the studied sites (Charlou et al, 2003;Herut et al, 2022;Huguen et al, 2009). The 18 O values of the Palmahim brine pools (+2.0‰ VSMOW ) are slightly enriched compared to ambient sea water (+1.5‰ VSMOW ; Herut et al, 2022).…”
Section: Lmc Cementsmentioning
confidence: 88%
“…They suggest multiple migration pathways of gas to the sea floor, with potential connectivity to the top of the Messinian evaporites unit and possibly also to deeper levels. In addition, recent discovery of combined brine and gas seepage at the northern part of the PD toe was associated by Herut et al (2022) with fluid flow from the Messinian evaporites. Tayber et al (2019) modelled the hydrate stability in the LB and correlated it with the observed seismic reflectivity.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…We collected one Idas specimen in 2011, from a carbonate sample that was retrieved from the Palmahim pockmark 32°09.6’N and 34°10.0’E at a depth of 1,036 m, using Hercules remotely operated vehicle (ROV), based on the Nautilus E/V. Multiple individuals were collected in 2021 from the edges of a brine pool at the toe of Palamhim disturbance, at 1,150 m water depth (32° 13.4’ N 34° 10.7’ E) [25], using the work-class SAAB Seaeye Leopard ROV, based on R/V Bat Galim ( Supplementary Fig. S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…We aimed to characterize the metabolism and physiology of the Idas symbionts, using genome-centric metagenomics, metatranscriptomics and metaproteomics. We collected 14 I. modiolaeformis individuals from hydrocarbon seeps and brine pools, off the shore of Israel [25, 26]. We hypothesized that the secondary symbionts may contribute to holobiont fitness by providing important functions, based on metabolic handoffs.…”
Section: Introductionmentioning
confidence: 99%
“…Tricyclic antidepressants have a significant impact on aquatic organisms, and the primary components in simulated seawater, K + , Na + , Ca 2+ , Mg 2+ , Cl − , F − , and I − , were used as interference agents. 52 IMH was added to the suspensions, and a blank was prepared without IMH. As shown in Fig.…”
Section: Luminescence Sensingmentioning
confidence: 99%